Pelatihan Desain Grafis sebagai Peningkatan Kreativitas dan Keterampilan Digital Siswa SMAN 1 Gowa - Sudirman; Musa; Nasir, Nasir; Henri; Ujianti Tawakkal (PT. Karya Inovatif Nusantara, 2025)
Graphic design skills are one of the skills that are increasingly needed in the digital era, both in the world of education and the creative industry. However, limited access and lack of training make high school students, especially at SMAN 1 Gowa, not have adequate skills in this field. This service aims to improve students' creativity and digital skills through practice-based graphic design training. Methods used include interactive lectures, live demonstrations, and self-practice using Adobe Photoshop and Canva software. This activity was attended by 30 students who were selected based on their interest and interest in graphic design. The results of the evaluation showed that 85% of the participants were able to understand the basic concepts of graphic design and produce simple design works with a good level of creativity. In addition, this training also increases students' confidence in participating in various design competitions and extracurricular activities. The conclusion of this activity is that graphic design training has a positive impact on the development of students' skills, as well as opening opportunities for them to contribute to school promotion activities and other creative projects.